Oxidation behaviors and mechanical properties of L12-strengthened high-entropy alloys at 700 ℃. (September 2022) - Liu, Shaofei; Kai, Wu; Hou, Jinxiong; Zhao, Yilu; Li, Qian; Yang, Chin-hua; Yang, Tao; Kai, Ji-jung
Abstract: Oxidation behavior and mechanical properties of two L12 -strengthened high-entropy superalloys (HESAs), i.e., (Ni2 Co2 FeCr)92 Ti4 Al4 and (Ni2 Co2 FeCr)92 Nb4 Al4, were systematically investigated at 700 ℃. Our results reveal that the oxidation resistance was significantly improved by the replacement of Ti with Nb with slightly optimized mechanical performance. The substitution of Ti by Nb promotes the formation of continuous Cr2 O3, AlNbO4, and Al2 O3 layers, and causes a remarkable improvement in oxidation resistance, thus highlighting the greater potential of Nb-bearing HESAs to function as the elevated-temperature structural materials. The underlying mechanisms for the superior mechanical properties and oxidation resistance of the Nb-bearing HESA were carefully discussed. Highlights: The oxidation behavior and mechanical properties of two different L12 -strengthened HESAs were studied at 700 ℃. The Nb-bearing HESA shows superior oxidation resistance than the Ti-bearing one without sacrifice of mechanical properties. The discontinuous Al2 O3 formed in the Ti-bearing HESA cannot effectively block cation diffusion. The low oxidation rate of the Nb-bearing HESA is attributed to the formation of triple-layered continuous oxide scales.